Knowledge, skills, and attitudes of teachers in training critical thinking of elementary school students - Suratmi Suratmi; Wahyu Sopandi (Journal of Education and Learning (EduLearn), 2022)
Knowledge, skills, and attitudes of teachers in developing critical thinking skills are very much needed to train students' basic thinking skills. This descriptive quantitative study described the knowledge, skills, and attitudes of teachers in developing critical thinking skills in elementary school students. The data collection employed a questionnaire with a Likert scale. The questionnaire was distributed online using Google Form during teacher professional development training. Respondents in this study were 366 elementary school teachers spread across 23 provinces in Indonesia. The data obtained were analyzed descriptively and quantitatively. The results of this study indicated the knowledge, skills, and attitudes of teachers in developing critical thinking in elementary school students are a good category. Description knowledge, skills, and attitudes of a good teacher impact the designed learning process. However, this study only described teachers' knowledge, skills, and attitudes in developing critical thinking skills, which the basis for implementing learning in elementary schools. The application of critical thinking learning by elementary school teachers can be used for further research.